METABOLITIC COMPLEX OF LACTOBACTERIA INFECTED WITH MULTI-RESISTANT STRAINS LELLIOTTIA AMNIGENA WOUNDS IN CONDITIONS IN VIVO - Olena Yu. Isayenko; Valerii V. Minukhin; Dmytro V. Minukhin; Denys O. Yevtushenko; Artem S. Lavrinenko; Vasiliy H. Hroma (Клінічна та профілактична медицина)
Aim. To study the antimicrobial activity of lactobacilli metabolites in order to create alternative antimicrobial agents with multifunctional activity.